Social media training as a marketing tool for micro-enterprises - Widi Hastomo; Ahmad Eko Saputro; Yoga Rarastro Putra (Community Empowerment, 2022)
Covid-19 has had a significant economic impact; MSMEs, which were so powerful during the 1998 economic crisis, were forced to abandon their operations during this pandemic. They must make mass layoffs in order to increase efficiency, without even providing severance pay to their employees. CV Sarana Teknik, which works in the furniture industry, had to lay off 93 percent of its employees due to a drop in turnover. The objective of the program is to provide digital marketing strategy counseling, training, and practice in the areas of interactive advertising content creation and ad management using the Facebook Ads Manager. The program is used a community development approach. This program broadened partners' understanding of digital marketing, particularly the use of Facebook ads and WhatsApp broadcasts. Despite the fact that the use of Facebook ads is still not optimal, sales turnover has increased in three months, particularly for innovative products such as dispenser mats.